The History of American Frontier and Its Record in Literary Works - Retnowati, Retnowati (Humaniora, 2013)
The spirit of frontier brought by the first settlers to America, has changed  in American continent and it was differently applied by the American government, especially when it became the motivation behind the expansion and anexation. This American frontier became the motivation of the American government to rule over the world. In the history of the American expansion, the spirit of American frontier was recorded in the literary works such as poerty, film, and novel.